2014
DOI: 10.7314/apjcp.2014.15.21.9185
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1297 Regulates the Growth, Migration and Invasion of Colorectal Cancer Cells by Targeting Cyclo-oxygenase-2

Abstract: Asian Pac J Cancer Prev, 15 (21), 9185-9190 IntroductionColorectal cancer (CRC) is one of the most common malignant tumors of the gastrointestinal tract. With an estimated 140 thousand new cases and over 50 thousand deaths in 2013, colorectal cancer (CRC) is the fourth most common cancer that leads to mortality in the United States (Committee et al., 2013). In addition, the incidence and mortality of colorectal cancer has continued to rise rapidly in China over the past few decades. The incidence of CRC has in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…The miRNAs are kind of endogenous non - coding RNA, they can negatively regulate the target genes expression on post - transcriptional level through binding to the 3′UTR of their mRNA [33]. The deregulation of miRNAs had been found in many human cancers, such as ovarian carcinoma [34], lung cancer [35,36], liver cancer [37], colon cancer [38, 39] and GBM [40]. MiRNA deregulation has become a new characteristic of malignant tumor, so some specific miRNAs are potentially novel biomarkers of cancer diagnosis and prognosis [41–45].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are kind of endogenous non - coding RNA, they can negatively regulate the target genes expression on post - transcriptional level through binding to the 3′UTR of their mRNA [33]. The deregulation of miRNAs had been found in many human cancers, such as ovarian carcinoma [34], lung cancer [35,36], liver cancer [37], colon cancer [38, 39] and GBM [40]. MiRNA deregulation has become a new characteristic of malignant tumor, so some specific miRNAs are potentially novel biomarkers of cancer diagnosis and prognosis [41–45].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-21 can regulate some important oncogenes or suppressor genes such as vascular endothelial growth factor (VEGF), phosphatase and tensin homolog (PTEN), etc. Therefore, higher expression of miR-21 in tumor tissue might indicate more aggressive of the tumor, such as colorectal cancer, breast cancer, gastric cancer, and liver cancer (19,(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-1297 inhibited prostate cancer cell proliferation and invasion by targeting the AEG-1/Wnt signaling pathway (18). miR-1297 inhibited the growth, migration and invasion of colorectal cancer cells by targeting cyclo-oxygenase-2 (19). These studies revealed that miR-1297 was a tumor suppressor.…”
Section: Introductionmentioning
confidence: 92%